EVALUATION OF GROWTH PERFORMANCE OF BROILER (COBB- 400) UNDER DIFFERENT COMPOSITION OF DIETS - RISHIKESH PATHAK,; NAZIM ALI,; SHALU KUMAR,; HARENDRA SINGH CHAUHAN, (The Bioscan, 2015)
The present experiment was conducted at Sardar Vallabhbhai Patel University of Agriculture and Technology Meerut to determine the growth performance of 40 broiler chicks after feeding them on four different dietary protein levels. All the birds were fed basal diets and in treatment group,birds were further supplemented with 24, 20 and 18 % different protein diets.Experiment was conducted for 42 days. Birds that fed different composition of diets show the significant (p<0.05) effect on feed intake, body weight gain and feed conversion ratio. Thus, the results show that the different dietary protein level having a significant effect on the growth performance of the broiler chicken